Development of Islamic-based sociodrama for the improvement of prosocial behavior - Sahrun Sahrun; Abdul Saman; Muhamad Anas (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2020)
The study aims to find out: (1) the needs analysis of Islamic-based sosiodrama models to improve prosocial behavior of students at Wahdah Makassar Middle School; (2) the prototype development of Islamic-based sosiodrama model to improve prosocial behavior of students at Wahdah Makassar Middle School; and (3) the validity and practicality of Islamic-based sociodrama models to improve prosocial behavior of students at Wahdah Makassar Middle School. The research approach was research and development (R&D). The research subjects consisted of 9 eighth graders at Wahdah Middle School in the 2019/2020 academic year. Data collection used interviews, documentation, and scale. Qualitative and quantitative data were analyzed. The results of the study showed that: (1) Islamic-based sociodrama models are needed at Wahdah Makassar Middle School; (2) Islamic-based sociodrama models are produced as guidance for counselors in improving students’ prosocial behavior; and (3) Islamic-based sociodrama models to improve prosocial behavior of students at Wahdah Makassar Middle School are declared valid and practical as a guide to Islamic-based sociodrama models based on accreditability testing, which includes: utility, feasibility, accuracy and content.